The diagnostic value of two-dimensional ultrasound Su-RADS combined with shear wave elastography for benign and malignant lesions of the gastric wall - Jingjing Xue; Guorong Lyu; Shaohui Li (BMC Medical Imaging)
Abstract Objective This study explored the value of stomach ultrasound reporting and data system (Su-RADS) and two-dimensional shear wave elastography (2D-SWE) in the diagnosis of benign and malignant lesions of the gastric wall, evaluating the feasibility of combining the two methods for the diagnosis of gastric wall lesions. Methods 113 patients with gastric wall lesions were examined after oral gastric ultrasound contrast agent, and the grades of the gastric wall lesions were classified according to Su-RADS. Moreover, 2D-SWE was performed to measure the E value of the lesions. ROC curves were constructed to evaluate the diagnostic efficacy of Su-RADS, 2D-SWE and their combination for gastric wall lesions. Results The cutoff values for Emean and Emax were 8.01 kPa and 11.08 kPa, respectively. The sensitivity and specificity of 2D-SWE were 70.59%, 93.67% and 85.69%, 88.61%, respectively. The diagnostic sensitivity and specificity of Su-RADS were 91.18% and 82.28%, respectively. The AUC of combination of two methods was 0.951, which was greater than that of Su-RADS (0.940) or 2D-SWE alone (0.853, 0.903), and the sensitivity and specificity were 82.35% and 94.94%. The sensitivity and specificity of the combination of the two methods for the diagnosis of malignant gastric lesions were 82.35% and 94.94%, respectively. The AUC was 0.951, and the Youden index was 0.8064. The DeLong test was used to determine the AUC between the combination of two methods and 2D-SWE was P < 0.05. Conclusion Compared with Su-RADS or 2D-SWE alone, the combination of the two methods is more effective at diagnosing of gastric wall.And improved the specificity in the diagnosis of gastric wall lesions.